Azadirachta indica: A herbal panacea in dentistry – An update - Lakshmi, T.; Krishnan, Vidya; R, Rajendran; Madhusudhanan, N. (Pharmacognosy Reviews)
Azadirachta indica commonly known as Neem, is an evergreen tree. Since time immemorial it has been used by Indian people for treatment of various diseases due to its medicinal properties. It possesses anti‑bacterial, anti‑cariogenic, anti‑helminthic, anti‑diabetic, anti‑oxidant, astringent, anti‑viral, cytotoxic, and anti‑inflammatory activity. Nimbidin, Azadirachtin and nimbinin are active compounds present in Neem which are responsible for antibacterial activity. Neem bark is used as an active ingredient in a number of toothpastes and toothpowders. Neem bark has anti‑bacterial properties, it is quite useful in dentistry for curing gingival problems and maintaining oral health in a natural way. Neem twigs are used as oral deodorant, toothache reliever and for cleaning of teeth. The objective of this article is to focus on the various aspects of Azadirachta indica in dentistry in order to provide a tool for future research.
Keywords: Azadirachta indica; anti‑bacterial; anti‑cariogenic; oral health